Optimization of CO2 Injection Through Cyclic Huff and Puff to Improve Oil Recovery - Dedi Kristanto; Hariyadi Hariyadi; Eko Widi Pramudyohadi; Aditya Kurniawan; Unggul Setiadi Nursidik; Dewi Asmorowati; Indah Widiyaningsih; Ndaru Cahyaningtyas (Scientific Contributions Oil and Gas, 2025)
One of the Enhanced Oil Recovery (EOR) strategies in the petroleum industry is CO2 injection using the huff and puff method. The method is performed on one well that acts as an injection and a production well. The method works by injecting a certain volume of carbon dioxide (CO2) gas into the reservoir and then closing the well for a period of time. This injection cycle can take place over several cycles. Production can be carried out after one or more cycles according to the design. In this study, CO2 injection optimization with the huff and puff method is carried out with reservoir simulation (GEM-CMG) by taking data from one of the oil and gas wells in Indonesia, with carbonate rock characteristics that are water wet. The simulation work steps include inputting data (fluid, rock properties, and production), initialization, history matching, and CO2 injection optimization with the huff and puff method. The optimization scenarios include optimization of injection pressure and number of cycles. The injection pressure scenario uses a range of 500 - 3000 psi, based on the simulation results obtained that the injection pressure of 500 psi produces the highest recovery factor (RF) of 22.2%. Then, the cyclic scenario was carried out at the optimum injection pressure (500 psi) with the number of cycles 2 - 6 cycles. From the simulation results, it is found that the number of cycles for this carbonate reservoir condition does not have a significant effect, as evidenced by the RF values ranging from 22.1 - 22.3%.